2017
DOI: 10.1080/00365521.2017.1335768
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in overweight patients with insulinoma: effects on weight loss

Abstract: Weight significantly decreased postoperatively in overweight insulinoma patients, which was more evident in patients with higher BMI and metabolic comorbidities were largely improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…Many factors possibly contributed to the postoperative weight loss [48], such as decreased food intake, elimination of hyperinsulinemia and surgical trauma. Similar to our results, Hongmei et al reported significant weight loss after surgery for a group of patients with insulinoma [49]. Their statistics showed than patients with high BMI (median BMI = 26.0 kg/m2) had a significant weight loss of 11.5 kg and %WL of 15.0% 3 months after surgery.…”
Section: Discussionsupporting
confidence: 90%
“…Many factors possibly contributed to the postoperative weight loss [48], such as decreased food intake, elimination of hyperinsulinemia and surgical trauma. Similar to our results, Hongmei et al reported significant weight loss after surgery for a group of patients with insulinoma [49]. Their statistics showed than patients with high BMI (median BMI = 26.0 kg/m2) had a significant weight loss of 11.5 kg and %WL of 15.0% 3 months after surgery.…”
Section: Discussionsupporting
confidence: 90%